THE LINGUISTIC ECOLOGY OF ENVIRONMENTAL CHANGE: ANALYZING THE DRIVERS AND PATTERNS BEHIND THE EMERGENCE OF NEW TERMS RELATED TO ECOLOGICAL SHIFTS - Abdullaeva Shakhlo Sayfievna (Modern American Journals, 2025)
This article explores the dynamic relationship between environmental change and linguistic evolution, specifically focusing on the emergence of new terminology reflecting ecological shifts. It employs a linguistic ecological framework to analyze the drivers and patterns behind this phenomenon, offering insights into how language adapts to and shapes human understanding of environmental transformations.
Keywords: Linguistic ecology, environmental change, neologisms, ecological shifts, socio-linguistics, cognitive linguistics, language evolution.